Behavioral Analysis of SME's Business Plan Preparation Before and After Running a Business: The Case Of Indonesia - Solihin, I.; Sujana, Fadhlan Ridhwana; Apriyani, Gina; Faritsal, Adam; Butar, D.J. Anderson Butar; Hidayat, Riski Taufik (CENTRAL ASIA AND THE CAUCASUS, 2022)
This paper aims to analyze the behavior of preparing a business plan before and after running a business. In this study, the period before starting a business is called the nascent period. While the period after running the business is called the start-up period. A business plan that is prepared during the nascent period is called a business plan. Meanwhile, the business plan prepared during the start-up period is called the experiential business plan. The research was conducted using primary data from 150 SME's respondents. The results show the experiential business plan has a bigger strategic role than the business plan prepared in the nascent period. The results also show that the preparation of business plans in the nascent period is mostly carried out by SME's with the opportunity entrepreneur motive than SME's with the necessity entrepreneur motive. Finally, the results of the study show that the part of the business plan that gets the most attention from SME's is the analysis of the marketing and financial functions.